Brexit and Western Balkans - Teokarević, Jovan (Bulgarian Journal of International Economics and Politics, 2021)
This article analyses effects of Brexit on relations between the United Kingdom and the Western Balkan countries (Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia, and Serbia). First, the symbolism of the UK departure from the EU for the Western Balkans is explained. In the following step, multiple types of relations (in trade, security, culture) between the post-Brexit UK and this region are analysed using the theoretical concepts of linkage, leverage and soft power. Finally, the consequences of Brexit on further EU enlargement are presented. The research has confirmed the initial hypotheses. First, as expected, the volume and density of UK-Western Balkan relations will be reduced after Brexit. Second, Western Balkans is of a very limited interest for the UK, primarily in security. Third, Brexit has not in a serious way changed the already existing low chances of EU accession for the Western Balkan countries. The reason for this has little to do with the UK’s presence in or absence from the EU and is rather a consequence of the majority view within the Union (that Britain had already shared before Brexit) concerning further enlargement and low level of preparation of Western Balkan countries for EU membership.
Keywords: Brexit; The United Kingdom; Western Balkans